Distinct immune profiles of recently exposed household contacts in a tuberculosis endemic setting in the Western Cape - Ngombane, Nokwanda Crystal (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScMedSc)--University of Stellenbosch, 2011.